2018
DOI: 10.1186/s12974-018-1253-y
|View full text |Cite
|
Sign up to set email alerts
|

Fas-ligand and interleukin-6 in the cerebrospinal fluid are early predictors of hypoxic-ischemic encephalopathy and long-term outcomes after birth asphyxia in term infants

Abstract: BackgroundCerebral ischemia generates neuroinflammation that can induce neural cell death. This cohort study assessed whether Fas-ligand (FasL) and interleukin (IL)-6 levels in the cerebrospinal fluid (CSF) after hypoxic-ischemic encephalopathy (HIE) can serve as biomarkers of hypoxic brain injury in neonates.MethodsTerm infants (> 37-week gestational age) who were admitted to the neonatal intensive care unit of Karolinska University Hospital in years 2002 to 2004 with perinatal asphyxia were enrolled prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
2
8
0
1
Order By: Relevance
“…It has been demonstrated that neuronal self-injury after exposure to LPS could be alleviated by using specific cytokine blockers, as it was already shown for IL-1beta [78]. On the other side, some cytokines like IL-6 has a dual function, where high levels early after HI insults are associated with adverse HIE outcomes; a secondary peak later after HIE was associated with better outcomes by regulating expression levels of IL-1beta and TNF-alpha [56,[82][83][84][85] and by its ability to promote neuronal differentiation of neural stem progenitor cells (NSPCs) and promote angiogenesis [86].…”
Section: Discussionmentioning
confidence: 91%
“…It has been demonstrated that neuronal self-injury after exposure to LPS could be alleviated by using specific cytokine blockers, as it was already shown for IL-1beta [78]. On the other side, some cytokines like IL-6 has a dual function, where high levels early after HI insults are associated with adverse HIE outcomes; a secondary peak later after HIE was associated with better outcomes by regulating expression levels of IL-1beta and TNF-alpha [56,[82][83][84][85] and by its ability to promote neuronal differentiation of neural stem progenitor cells (NSPCs) and promote angiogenesis [86].…”
Section: Discussionmentioning
confidence: 91%
“…Information was gathered from outpatient paediatric care centres on the outcomes of the control group when they were 18 months of age. Some of the clinical characteristics of a subgroup of the recruited infants have previously been published 12 …”
Section: Methodsmentioning
confidence: 99%
“…Поскольку концентрации IL-6 и FasL в спинномозговой жидкости положительно коррелируют с плохими 18-месячными клиническими исходами (p <0,0001), они могут быть полезны в качестве биомаркеров тяжести гипоксического по-вреждения головного мозга и для прогнозирования отдаленного исхода, в том числе риска ДЦП после перинатальной асфиксии. Комбинация этих маркеров повышает их прогностическую ценность [25].…”
Section: биомаркеры воспаленияunclassified